Contentious Politics in the Middle East Popular Resistance and Marginalized Activism beyond the Arab Uprisings - Gerges, Fawaz A. 1958- (Middle East Today, 2015)
Cover -- Title -- Copyright -- Contents -- List of Illustrations -- Acknowledgments -- Introduction Contextualizing the Arab Spring Uprisings: Different Regimes, Different Revolutions, and Different Trajectories -- PART I Rethinking Contentious Politics: History and Theory -- CHAPTER 1 Contention and Constitutionalization in the Global Realm: Assessing the Uprisings in West Asia and North Africa and Their Impact on International Politics -- CHAPTER 2 Reconceptualizing Resistance and Reform in the Middle East